PREFERENSI KONSUMEN TERHADAP PERMINTAAN JASA PEMOTONGAN AYAM DI KECAMATAN KEMANGKON DAN BUKATEJA KABUPATEN PURBALINGGA - alfian maulana; Soegeng Herijanto; Citopartusi Tjahyani; Tri Sukmaningsih (MEDIA PETERNAKAN, 2024)
This study aims to determine the effect of adding papaya leaf flour to the feed on feed consumption and feed conversion in 6-10 week old Manila ducks. This study used 40 male Manila ducks divided into 4 treatment groups with 5 replications, namely P0 (control), P1 (2% papaya leaf flour), P2 (4% papaya leaf flour), and P3 (6% papaya leaf flour). The research results indicate that the addition of papaya leaf flour does not have a significant effect (P>0.05) on feed consumption and feed conversion in Manila ducks. However, numerically, the highest feed consumption was found in P0 (657.30 grams/head/week) and the lowest feed conversion in P2 (4.33). It is recommended to use 4% papaya leaf meal in the Manila duck feed for feed efficiency